1988
DOI: 10.1002/bip.360271206
|View full text |Cite
|
Sign up to set email alerts
|

Helix–Coil transition of plasmid dna by adiabatic differential scanning microcalorimetry

Abstract: SynopsisAdiabatic differential scanning microcalorimetry, which provides curves of the heat capacity vs temperature, was carried out for the DNA of plasmid pJL3-TB5 (5277 base pairs in length). The calorimetry curve shows nine peaks ranging from 81 to 96°C in 1 X SSC buffer at a heating rate of 0.25'C, due to the stepwise helix-coil transition of the DNA along the molecular chain. The theoretical melting curve, which can be constructed by calculation from the entire nucleotide sequence of the plasmid DNA by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is possibile that the dam methylated DNA is recognized by a certain initiator protein in DNA replication, as previously discussed ( 2 ). However, it has been clearly demonstrated that the local stability of the helix-ciol transition along the DNA chain is closely related to the functional regions, such as transcriptional promoters, terminators, and the protein coding regions of genes ( 16,17,20 ). Our observation of facilitation in melting of the oriC region caused by dam methylation at GATC may thus have a significant role in initiation of DNA replication.…”
Section: W1mentioning
confidence: 72%
“…It is possibile that the dam methylated DNA is recognized by a certain initiator protein in DNA replication, as previously discussed ( 2 ). However, it has been clearly demonstrated that the local stability of the helix-ciol transition along the DNA chain is closely related to the functional regions, such as transcriptional promoters, terminators, and the protein coding regions of genes ( 16,17,20 ). Our observation of facilitation in melting of the oriC region caused by dam methylation at GATC may thus have a significant role in initiation of DNA replication.…”
Section: W1mentioning
confidence: 72%
“…Thermal perturbation combined with measurements of circular dichroism (CD), 1 UV absorption, 2,3 and differential scanning calorimetry (DSC) 4 have been commonly used to probe the structural and energetic changes of linear polynucleotides (which melt below 1008C) and to evaluate the effects of polycations and ionic strength upon nucleic acid stability. Recent improvements in the sensitivity and temperature range (up to 1258C) of modern pressurized differential scanning calorimeters, 5 however, allow the evaluation of the thermal stability of supercoiled (SC) DNA (which can unfold above 1008C) without the use of chaotropic agents to lower its denaturation temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Eastman (5) has proposed that cis-DDP binds to the DNA sequences 5'-GG-3', 5'-AG-3' and 5'-GNG-3' on one strand to which the binding probability of cis-DDP is 0.65, 0.25 and 0.06, respectively. Maeda et al (11,12) showed that each peak in the DSC curve can be assigned to the particular regions of the nucleotide sequence under the helix-coil transition theory. Therefore, to know whether the binding of cis-DDP to the particular sequences affects DSC curve, the cis-DDP binding sites proposed by Eastman on one strand of pJL3-TB5 DNA were counted, and the Temperature (°C) Fig.…”
Section: And Discussionmentioning
confidence: 99%